The tale of Whitefoot - Brandhorst, Carl T.; Sylwester, Robert (New York, Simon & Schuster, 1968)
Explains how the molecules of Whitefoot, a dead garden mouse, are transformed into useful substances that live again in other animals and plants.
Keywords: Ecology -- Juvenile literature; Ecology